Computational Simulation of Fracture of Materials in Comminution Devices - Gutierrez-Silva, A (Elsevier Ltd, 2014)
Three different comminution devices: crushers, mills and hybrid-mills (a synergistic combination of a mill and a crusher) are studied. To achieve the objective, benchmarking was performed for the three devices. Specifically, a computer code was developed based on the discrete element method (DEM), which is capable of capturing comminution variables such as material fracture, load motion, power consumed, and number of impacts, among others. The milled material has been modeled through a set of spheres (basic elements of DEM), joined together by beam elements similar to those used in the finite element method (FEM). The beams have mechanical properties that are defined by the type of material being ground and they can be broken through a failure criterion established by the stress level attained. The comparison is made on equal terms for the three devices, using the same size and granulometric distribution of the material to be ground. The hybrid mill has advantages over the other two particular case of operation.